ANALISIS LAPORAN KEUANGAN PNPM MANDIRI KECAMATAN BLORA KABUPATEN BLORA BERDASARKAN STANDAR AKUNTANSI PEMERINTAHAN - Anton Sumbogo (Universitas Slamet Riyadi, 2015)
Analisis Laporan Keuangan PNPM Mandiri Kecamatan Blora Kabupaten Blora … (Anton S.) 33ANALISIS LAPORAN KEUANGAN PNPM MANDIRI KECAMATAN BLORA KABUPATEN BLORA BERDASARKAN STANDAR AKUNTANSI PEMERINTAHAN Anton Sumbogo Program Studi Akuntansi Fakultas Ekonomi Universitas Slamet Riyadi Surakartae-mail: sumbogo31@gmail.com ABSTRACT Program Nasional Pemberdayaan Masyarakat Mandiri (PNPM-Mandiri) is a program that was launched to enable people to escape from poverty. In performing the duties required to make the work unit's financial statements in accordance with Government Accounting Standards. Government Accounting Standards are set out in Accounting Principles in preparing and presenting financial statements of the Government. This study aims to determine the format that has been reported so far that contains the disclosure and presentation of the financial found are reported. The method used is descriptive comparative analysis. Data obtained through field research is to conduct interviews at the Economic Facilitator and collecting records and documents with the object being studied relating to Financial Statements PNPM Mandiri. The population used in this study is the facilitator District of Blora area. Sampling in research using purposive sampling method is based on the population of the largest and most productive age. The results showed that faskel in running the PNPM Mandiri has records of all activities undertaken but still there is a difference between a report presented by the Government Accounting Standards, due to factors such as bureaucracy, human resources, communication and attitude. Keywords: Akuntansi, Laporan Keuangan, Sektor Publik, PNPM Mandiri